A rare case of ophiasis pattern of alopecia areata in a child: a case report with Unani insights - Farooqui, Uzma I.; A. Afzal, Shaikh M.; Jamal, Mohammad A.; Muzammil, Mohammad; Ilyas, Juwairiya (International Journal of Research in Medical Sciences, 2025)
Alopecia areata is a T cell–mediated autoimmune disease targeting hair follicles. Ophiasis is a rare subtype of alopecia areata with a snake-like hair loss pattern across the occipital, temporal, and parietal scalp. A 3-year-old Indian boy presented with a 4-month history of patchy scalp hair loss. Clinical and trichoscopic examination confirmed rare pattern of ophiasis type of alopecia areata. Ophiasis pattern of alopecia areata is considered one of the most challenging forms to treat, owing to its chronic and relapsing nature as well as its poor response to conventional therapies. In this context, the present paper attempts to provide a foundational perspective on the management of ophiasis through the Unani system of medicine.